High Light Intensity Applied Shortly Before Harvest Improves Lettuce Nutritional Quality and Extends the Shelf Life - Min, Qianxixi; Marcelis, Leo F. M.; Nicole, Celine C. S.; Woltering, Ernst J. (Frontiers in Plant Science, 2021)
The effect of light intensity applied shortly before harvest on the nutritional quality, postharvest performance and shelf life of loose-leaf lettuce (Lactuca sativa L. CV. Expertise RZ Salanova®) was investigated. Lettuce was grown either in a greenhouse with supplemental high-pressure sodium (HPS) light (Experiment 1, EXP 1) or in a climate room under white LED light (Experiment 2, EXP 2). In both experiments full grown plants were transferred to a climate room for the End of Production (EoP) light treatments during the last week of cultivation. During EoP lighting plants were exposed to different intensities (0, 110 and 270 µmol m-2 s-1 in EXP 1; 50, 210, 470 µmol m-2 s-1 in EXP 2) from white-red LEDs for 6 (EXP 2) or 7 days (EXP 1). Mature leaves were then harvested and stored in darkness at 10 ℃ to study the postharvest performance. Changes in dry matter content, total ascorbic acid and carbohydrates (including glucose, fructose sucrose and starch) levels were determined during EoP lighting and during the subsequent shelf life as indicators of lettuce nutritional quality. Quality aspects (appearance, texture and odour) were accessed during the shelf life as indicators of postharvest performance. In both experiments, high light intensities applied in EoP lighting increased dry matter percentage and contents of ascorbic acid and carbohydrates at harvest and these increased levels were maintained during the shelf life. Increased light intensity in EoP treatment also extended the shelf life. The levels of ascorbic acid and carbohydrates at harvest correlated positively with the subsequent shelf life, indicating that the prolonged shelf life relies on the improved energy and antioxidant status of the crop at harvest.